Institution building in India : some experiences - Philip, J. (Joe) (Mumbai : Himalaya Pub. House, 2007)
Autobiographical reminiscences of academician of management education, his association and contribution in leading educational and management training institutions in India.
Includes bibliographical references.
Keywords: Philip, J; Management -- Study and teaching -- Biography; Research institutes -- India -- Administration -- Biography